1999
DOI: 10.1006/jagm.1998.0993
|View full text |Cite
|
Sign up to set email alerts
|

Greedy Strikes Back: Improved Facility Location Algorithms

Abstract: A fundamental facility location problem is to choose the location of facilities, such as industrial plants and warehouses, to minimize the cost of satisfying the demand for some commodity. There are associated costs for locating the facilities, as well as transportation costs for distributing the commodities. We assume that the transportation costs form a metric. This problem is commonly referred to as the uncapacitated facility location (UFL) problem. Applications to bank account location and clustering, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
388
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(399 citation statements)
references
References 18 publications
9
388
0
2
Order By: Relevance
“…We show that if the instance is (α, ǫ)-perturbation resilient with α > 2 + √ 3, then we can in polynomial time output a clustering that provides a (1 + 5ǫ/ρ)-approximation to the optimum, where ρ is the fraction of the points in the smallest cluster. Thus this improves over the best worst-case approximation guarantees known [20] when ǫ ≤ √ 3ρ/5 and also beats the lower bound of (1 + 1/e) on the best approximation achievable on worst case instances for the metric k-median objective [17,18] when ǫ ≤ ρ/(5e).…”
Section: (α ǫ)-Perturbationsupporting
confidence: 58%
“…We show that if the instance is (α, ǫ)-perturbation resilient with α > 2 + √ 3, then we can in polynomial time output a clustering that provides a (1 + 5ǫ/ρ)-approximation to the optimum, where ρ is the fraction of the points in the smallest cluster. Thus this improves over the best worst-case approximation guarantees known [20] when ǫ ≤ √ 3ρ/5 and also beats the lower bound of (1 + 1/e) on the best approximation achievable on worst case instances for the metric k-median objective [17,18] when ǫ ≤ ρ/(5e).…”
Section: (α ǫ)-Perturbationsupporting
confidence: 58%
“…These two results are very close to the best possible approximation factor in that [GUHA98] have shown that we cannot get an approximation factor below 1.463 in polynomial time unless NP ⊆ DTIME[n O(log log n) ].…”
Section: Connection Costsupporting
confidence: 74%
“…The algorithmic concepts can be based on LP-rounding [15,16] or on primal-dual approach [17,18]. The 1.52 approximation ratio that has been obtained in most recent studies is close to the lower bound proved in [19]. Many variants of FLP have been studied; most of them are NP-hard [20].…”
Section: Related Workmentioning
confidence: 86%